Career and identity as flexible resources in talk: a discourse analysis of graduate employees' accounts of work experience - Coupland, Christine (2001)
'Career', as a term, has been described as difficult to define yet frequently used, as if it is commonly understood what it means. Its relevance as a topic of investigation lies in its prevalence in people's accounts of themselves and their work. There has been a growing awareness of the constructed nature of the term 'career' which merits new empirical research. In addition, the relationship between identity and career from a constructionist perspective has rarely been explored. In the present thesis an empirical investigation of graduate employees' talk about workplace experiences aims to add to understanding about career and identity as resources which may be drawn on in interaction.